Essential Oils and Their Formulations for the Control of Curculionidae Pests - Garrido-Miranda, Karla A.; Giraldo, Juan D.; Schoebitz, Mauricio (Frontiers in Agronomy, 2022)
Pesticides are widely used in producing food to control pests. However, it has been determined that synthetic pesticides present severe toxicity (residual), while they also result in environmental contamination and development of high-level resistance in some insect species. Due to this, some of these susbtances have been banned or restricted in many countries, which has reduced the number of agrochemicals that can be used for pest control, particularly in the case of crops exported to green markets such as Europe and Asia. Under this scenario, essential oils (EOs) are being increasingly studied as bioinsecticides because they are renewable, natural, biodegradable, non-persistent in the environment and safe to non-target organism and humans. It has been determined that EOs have repellent, ovicidal, larvicidal, and insecticidal effects against different types of pests, but they also have some drawbacks due to their high volatility and low aqueous solubility. This mini-review focusses on EOs used as bioinsecticides for the control of Curculionidae and on current stabilization techniques, such as nanoencapsulation, to prolog the biocidal effect of EOs against these pests.